Revisiting Indonesia’s Zakat Law: Legal Analysis of Marine Product Zakat and Reform Proposals - Muhasim, Ahmad; Amrulloh, Moh. Asyiq; Abdullah, Abdullah; Rahman, Azman AB (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2025)
Research on the zakat (charitable giving) related to marine products in Indonesia is currently limited. Given the vast economic potential of these resources, the existing regulations have not adequately kept pace with developments in the marine sector. This study aims to examine the legal framework governing zakat on marine products in Indonesia, pinpoint weaknesses in the current laws, and suggest reforms to create a more equitable and functional zakat system. Using a normative juridical approach, the research primarily focuses on the statutory basis for necessary legal changes. The findings reveal that the existing regulations regarding zakat are encapsulated in Law No. 23 of 2011 on Zakat. A significant flaw identified in this law lies in Article 4, Paragraph (2), which fails to specifically recognize certain marine products as zakat objects. Notably, products such as coral reefs, salt, pearls, seaweed, and revenue from marine tourism are not listed among zakat maal (zakat on assets). To address this shortcoming, it is essential to amend the law by adding to Article 4, paragraph (2) the phrase "Other marine products that have high economic value, including but not limited to pearl shells, marine biota for pharmaceuticals and cosmetics, lobsters, mangrove crabs, seaweed, and other marine resources." This amendment is crucial to eliminate legal ambiguities, ensuring there are clear regulations and categorizing marine products as eligible for zakat.